Identity, Religion and Legitimacy: The Dynamics of Immigrants in Managing Halal Certification in Malaysia - Ahmad Yoga; Nafi'ah Nafi'ah; Ning Daris Salamah Elmi Putri Sibron Ning; Khoirul Fathoni Khoirul Fathoni (El-Barka Journal of Islamic Economics and Business, 2026)
This study examines how Muslim immigrants in Malaysia navigate and adapt to the halal certification process, and how it serves as a means to establish a religious identity and a source of legitimacy for their business activities. The study used a qualitative approach, employing in-depth interviews with 12 informants, including Indonesian Muslim immigrant food entrepreneurs, Muslim consumers, and community leaders in Gombak, Selangor, Malaysia. Data was obtained through interviews, observations, and documentation, then analyzed using Miles and Huberman's interactive model. It is interpreted using the theoretical framework of social identity, symbolic interaction, and institutional legitimacy. Findings show that the status of immigrants formally does not hinder the halal certification process as long as all administrative and Sharia standards are met. However, immigrants still face obstacles such as bureaucratic complexity, language barriers, the digitization of the MYe-HALAL system, and strict documentation requirements. Conclusion, in practice, halal certification serves not only as a form of regulatory compliance but also as a symbol that can increase consumer trust and strengthen social acceptance of immigrants. This study contributes to the study of halal governance by showing that halal certification functions not only as a regulatory mechanism, but also as an instrument of social legitimacy and economic integration for Muslim immigrant entrepreneurs.